PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - SADIYAH, KHALIMATUS; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2019)
This research aims to determine the effect of corporate governance mechanisms that are proxies through institutional ownership, managerial ownership, independent commissioners and independent directors on firm value. This research uses multiple linear regression analysis. The research sample is a company incorporated in the property, real estate and building construction sector period of 2015-2018 with a total data of 193. The results of this study indicate that the independent commissioners and independent directors has effect on firm value.